Faith formation in the tension interplay of tools, processes and the course for social transformation - M Moyo; K.J. Pali (Acta Theologica)
Theological commentators indicate that the church in Africa faces the challenge of converting the Christian faith into practice. This calls for reconsidering the practice of forming faith among African churches. According to Astley (2018:16), in Christianity, faith formation is more than learning about Christ; it is about “learning” Christ. Learning Christ as Christian formation constitutes the shaping of the dimensions of faith, namely orthopraxis, orthopatheia, and intelligentia (Maddix et al. 2020:6). This article discusses Gadamer’s conversation theory as the means to inform and form these dimensions of faith. This entails that, for faith to be informed and formed in its dimensions, there is a need for an effective conversation among tools, processes, and contexts. The discussion revolves around the following question: How can the tools and processes of faith formation effectively converse with context in order to facilitate the learning of Christ in terms of informing and forming these dimensions of faith? Using conversation theory and literature review, this article discusses the tension interplay of tools, processes, and discerning contexts for a holistic approach to informing and forming the dimensions of faith.